2011
DOI: 10.5539/jas.v4n3p259
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Grain and Food Quality Traits of Some Indigenous Rice Cultivars of North-eastern Hill Region of India

Abstract: Searching rice cultivars or variety with good processing and high in important essential nutrients are prime important in the present context of rice research. The north eastern hill region of India which is a mega biodiversity hot spot of the world has numerous cultivars of rice with tremendous potential of high quality rice. Eighteen indigenous cultivars of Tripura, a north eastern hill state of India were subjected to the study. Majority of the cultivars were of short bold grain type. Eleven cultivars were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…The amylose content had high heritability and genetic advance suggesting that selection for this trait would improve the genotypic value of the selected plants over those of their parents. These results lend credence to the work conducted by Thongbam et al (2012) and later by Nirmaladevi et al (2015), wherein they noted a high amylose content heritability and genetic advance and also suggested that selection for this trait would improve the genotypic value of the selected plants over those of their parents. They further pointed out that the protein content heritability was moderately high while genetic advance was very low due to low genotypic variation and influence of environmental factors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The amylose content had high heritability and genetic advance suggesting that selection for this trait would improve the genotypic value of the selected plants over those of their parents. These results lend credence to the work conducted by Thongbam et al (2012) and later by Nirmaladevi et al (2015), wherein they noted a high amylose content heritability and genetic advance and also suggested that selection for this trait would improve the genotypic value of the selected plants over those of their parents. They further pointed out that the protein content heritability was moderately high while genetic advance was very low due to low genotypic variation and influence of environmental factors.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, to breed for improved quality, it is important that breeders acquaint themselves with sound knowledge concerning the inheritance of rice quality traits. Thongbam et al (2012) demonstrated that the amylose content of rice had high heritability and genetic advance, suggesting that the selection for this trait could improve the genotypic value of the selected plants over those of their parents. The heritability for protein was moderately high, but the genetic advance was very low due to low genotypic variance (GCV) and because of more influence of the environmental factors; therefore, simple phenotypic selection may not bring its genetic improvement.…”
Section: Introductionmentioning
confidence: 98%
“…Starch isolated from grains of var. NDR97, a traditional variety of indigenous "Bororice" which is known to have low (4%) AAC [27], was used as a reference for purposes of comparison.…”
Section: Determination Of Apparent Amylose Contentmentioning
confidence: 99%
“…High carbohydrate content in rice indicates good source of energy. Rice is a poor source of protein but it has high quality protein (lysine) because of its unique nutritional composition (Thongbam et al, 2012). Protein content in most of the studied ranged from 5.3 to 11.5% (Thongbam et al, 2012;Diako et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Rice is a poor source of protein but it has high quality protein (lysine) because of its unique nutritional composition (Thongbam et al, 2012). Protein content in most of the studied ranged from 5.3 to 11.5% (Thongbam et al, 2012;Diako et al, 2011). Fat content of rice ranges from 0.5 to 3.5% (Oko and Ugwu, 2011) but the bran of rice is known by its high fat content up to 22.5% in some traditional varieties (Ravi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%